Bio‐Inspired Binder Design for a Robust Conductive Network in Silicon‐Based Anodes. Issue 5 (9th March 2022) - Song, Zhibo; Zhang, Taohang; Wang, Lu; Zhao, Yan; Li, Zikun; Zhang, Meng; Wang, Ke; Xue, Shida; Fang, Jianjun; Ji, Yuchen; Pan, Feng; Yang, Luyi
Abstract: Due to the severe volume variations during electrochemical processes, Si‐based anodes suffer from poor cycling performance as the result of a collapsed conductive network. In this regard, a key strategy for fully exploiting the capacity potential of Si‐based anodes is to construct a robust conductive network through rational binder design. In this work, a bio‐inspired conductive binder (PFPQDA) is designed by introducing dopamine‐functionalized fluorene structure units (DA) into a conductivity enhanced polyfluorene‐typed copolymer (PFPQ) to enhance its mechanical properties. Through constructing hierarchical binding networks and resilient electron transportations within both nano‐sized Si and micro‐sized SiOx electrodes via interweaved interactions, the PFPQDA successfully suppresses the electrode expansion and maintains the integrity of conductive pathways. Consequently, owing to the favorable properties of PFPQDA, Si‐based anodes exhibit improved cycling performance and rate capability with an areal capacity over 2.5 mAh cm –2 . Abstract : Facing the challenge of cycling stability and rate performance issues in Si‐based anodes, a bio‐inspired conductive binder is designed and employed. Its unique molecular structure facilitates a hierarchical binding network consisting of strong covalent bonds and dynamic hydrogen bonds in Si‐based electrodes, boosting the mechanical robustness of electron transfer networks during prolonged cycling.